Efficacy of imazamox with centrifugal energy spray nozzle on eichhornia crassipes and economic analysis of control viability - Garlich, N. [UNESP]; Guarnieri, C. C.O. [UNESP]; Freitas, R. L.G. [UNESP]; Cervoni, J. H.C.; Cruz, C.; Ferreira, M. C. [UNESP] (FapUNIFESP (SciELO), 2019)
The efficacy of imazamox to control Eichhornia crassipes with a centrifugal energy spray nozzle at doses and volumes of spray solution and the costs of mechanical and chemical control of aquatic plants were evaluated in this study. Imazamox doses consisted of 200, 400, and 600 g a.i. ha-1, and spray solution volumes consisted of 25, 50, and 100 L ha-1, with a control (without herbicide application) and ten replications. Applications were performed with a centrifugal energy spray nozzle. The evaluations were carried out considering the percentage of control at 7, 15, 21, and 30 days after application (DAA), and plant dry matter was measured at 30 DAA, as well as leaf retention of spray solutions. An efficacy from 96 to 100% and plant dry matter reduction from 88 to 100% was observed at 30 DAA using imazamox doses of 200, 400, and 600 g a.i. ha-1 and a spray solution volume of 50 L ha-1. Imazamox doses and spray solution volumes were effective in controlling E. crassipes, except for 200 g a.i. ha-1 and 25 L ha-1, respectively. The highest leaf retention of E. crassipes was 0.010 mL cm2 at an imazamox dose of 400 g a.i. ha-1 and volume of 50 L ha-1. The cost of chemical control was 20 times lower when compared to mechanical control, making it economically more viable. These results are important for decision-making on which method and application technology should be used to control E. crassipes.
Eficácia do imazamox com bico de pulverização de energia centrífuga em eichhornia crassipes e análise econômica de viabilidade de controle
Keywords: Application technology; Common water hyacinth; Eichhornia crassipes; Management